ANALYSIS OF GIVING EARLY ASI, ASSEMBLY WITH NUTRITION STATUS IN BABY AGE 0 - 6 MONTHS IN POSYANDU VILLAGE SIWALANPANJI BUDURAN SIDOARJO - firdaus firda firdaus (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
There are still many parents who give MP-ASI early that may resulting in excess nutritional risks in infants.The purpose of this study is to determine the relationship between an early breastfeeding with nutritional status in infants aged 0-6 months in Posyandu Desa Siwalanpanji Buduran Sidoarjo.This research uses observational analytic design with cross sectional approach. The population was 35 mothers and infants aged 0-6 months. The sample was 32. The Sampling technique using probability sampling with simple random sampling. The independent variable is the provision of early breast milk and the dependent variable is the nutritional status. The instrument used is questionnaire. The statistical test using Mann Whitney. The results of the study were almost entirely of respondents (84.4%) gave early-breast-feeding (MP-ASI) and most of them (59.3%) had more nutritional status. The result of Mann Whitney test with significance level α = 0,05 got value ρ = 0,017 and α = 0,05. Thus ρ <α then H0 is rejected which means there is a relationship between the giving of early breastfeeding with nutritional status of infants aged 0-6 months.Early breastfeeding may cause the baby have more nutritional status and be at risk of obesity. It is expected that health practitioners provide health education related to the the correct procedure of giving MP-ASI, the benefits of breastfeeding, and the risk of more nutritional. Keywords: early breastfeeding food, nutritional status